Technology and Skill Demand in Mexico - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2013)
The author investigates the effects of technology on the employment and wages of differently skilled Mexican manufacturing workers using firm panel data from 1992-99. She analyzes the relationship between technology and skill demand. Findings support the skill-biased technical change hypothesis. She then examines the temporal relationship of technology adoption to firm productivity and worker wages. The author finds that skilled labor increases after technology adoption. And wages of both skilled and semi-skilled workers exhibit markedly increased growth rates compared with the growth rate of low-skilled workers. The results show that investment in human capital improves technology-driven productivity gains.